2022
DOI: 10.1089/cyber.2021.0050
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Health Factors and Psychological Well-Being in Gaming Disorder

Abstract: The recent recognition of Gaming Disorder (GD) as a mental health issue has provided a unique opportunity for researchers to advance our current understanding of the intricate relationships between GD and specific health-related factors and well-being. The present study sought to investigate the role of key physical and psychological health and well-being factors in GD. To achieve this, the three goals were explored. First, we tested whether GD can be predicted by health and well-being factors such as depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…It should also be noted that more recent studies also reported links between GD and psychological problems in daily life (e.g. Männikkö et al, 2020;Moore et al, 2022).…”
mentioning
confidence: 94%
“…It should also be noted that more recent studies also reported links between GD and psychological problems in daily life (e.g. Männikkö et al, 2020;Moore et al, 2022).…”
mentioning
confidence: 94%
“…In terms of gaming behaviors, excessive engagement with the activity can become an addiction upon the experience of functional impairments [12,13], with a recent large-scale international study of more than 123,000 gamers reporting that disordered gaming may translate to 34.53 to 40.13 hours of weekly time spent gaming [14]. It is widely known that disordered gaming may negatively impact both mental and physical health, cognitive, social, academic, and occupational functioning [7,[15][16][17]. Disordered gamers display signs of addiction including tolerance, salience, mood-swing, losing control, covering up and risking significant relationships or opportunities [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, a confounding factor (i.e., gaming disorder (GD)) was not evaluated in this study. GD is a mental health issue, which intricates relationships with specific health-related factors and well-being [ 65 ]. A recent study including 474 participants aged 18–66 years reported that age, attention problems and physical health problems significantly predicted GD [ 64 ].…”
Section: Discussionmentioning
confidence: 99%